Prevalence of Intermediate Syndrome among Admitted Patients with Organophosphorous Poisoning in a Tertiary Care Hospital - Uprety, Ananta Bhakta (JNMA J Nepal Med Assoc, 2019)
INTRODUCTION: Organophosphorous poisoning is a common problem prevalent in Nepal. Intermediate syndrome is a common clinical feature seen among the patients those have ingested poison. There is a scarcity of data related to intermediate syndrome and other general complications in patients with organophosphorous poisoning in context of Nepal. This study was carried out to observe the prevalence of intermediate syndrome and the general complications of oraganophosphorus poisoning among admitted patients in a tertiary care hospital. METHODS: This was a descriptive cross-sectional study conducted at a tertiary care hospital from April 2008 to June 2009 after ethical approval was from Institiutional Review Board of tertiary care hospital. Forty four patients with history of ingestion of organophosphorus poisoning within 24 hours were included in our study through convenience sampling. Clinical examinations were done to look for Intermediate syndrome. Data was entered in Statistical Package for Social Sciences and point estimate at 95% of CI was calculated along with frequency and proportion for binary data. RESULTS: Out of 44 patients, features of intermediate syndrome were seen in 40 (90.9%) at 95% of CI (84.2-97.6) patients in the study. The frequency of intermediate syndrome signs like weakness of neck flexion, inability to sit up and swallowing difficulty were seen among the patients. Complications like pneumonia 4 (9.09%), hyponatremia 3 (6.8%), hypokalemia 1 (2.27%) and bradycardia 1 (2.27%) were seen in the study. Mortality seen in the study was 2 (4.5%) among the admitted patients. CONCLUSIONS: Prevalence of intermediate syndrome was higher compared to other studies done in similar settings. Complications like pneumonia, hyponatremia, hypokalemia and bradycardia were seen among the patients.